PENYULUHANPERENCANAAN BANGUNAN TAHAN GEMPA - ari Wibowo (UII, 2013)
Damage to buildings caused by natural disasters caused by the low quality ofmaterials and building techniques are not in accordance with the rules of construction. Aserious concern for all people of the dangers of an earthquake happens, so does thesocialization construction of earthquake-resistant homes in order to provide anunderstanding or provide knowledge to the public about how the importance of having ahome stay that had earthquake-resistant structures. The goal is that people feel safe if abigearthquake that occurred in the region of Central Java and in case of building damagedoes not occur in the structure so it can save costs in renovating residential buildings.As a result of the extension planning earthquake-resistant buildings is a reference insociety have built houses that were living in it feel safe.